INKLUSIVITAS DAN KELESTARIAN: PROGRAM PEMBERDAYAAN DIFABEL MELALUI KEWIRAUSAHAAN BERBASIS ECO-FRIENDLY - Azharotunnafi, Azharotunnafi; Amalina, Sharfina Nur; Abdani, Fadlil (As-Sidanah, 2025)
This paper aims to explain how eco-friendly-based training impacts people with disabilities. The mentoring training aims to provide opportunities for LINKSOS people with disabilities to have independence and entrepreneurial skills that are environmentally friendly. The method used is ABCD, namely Asset-Based Community Development, which uses an approach to assets or potential, where the community already has skills in making marketing and MSME (Micro, Small, and Medium Enterprises) businesses developed. Hence, the service team tries to add skills with eco-friendly training. This activity lasted for 2 days. First, introducing the concept of entrepreneurship and how to start an easy business. The second day was to train people with disabilities who have limitations so that they can still work and produce entrepreneurial opportunities with environmentally friendly principles, namely by ecoprinting with totebag media. This training resulted in: (1) People with disabilities understand the entrepreneurial skills needed to be economically independent and have business opportunities; and (2) People with disabilities understand and can practice making Ecoprint with totebag media. This activity has implications for people with limitations to be able to work by utilizing materials that are easily obtained in the surrounding environment.